Biochemical and Microbiological Safety Risks in Salted Fish Products: A Review - Nosić, Mario (Food and Drug Safety, 2026)
Salting is one of the most widely used fish processing methods, although fish prepared in such a way is exposed to many biochemical changes. There is still insufficient information on the mechanisms of reactions that occur during salting, so the process is still conducted on an experimental basis. Sodium chloride (NaCl) reduces water activity values and consequently has an antimicrobial effect on salted fish products. The main changes that happen during this process are: protein loss, lipid oxidation, enzymatic activity, and growth of halophilic bacteria. In this paper, an extensive literature review has been made on the topic of previously listed changes that occur during fish salting, and it is expected that it will broaden the picture of biochemical changes during fish salting with the aim of developing a safer and more effective procedure concerning the health of the final consumer. Staphylococcus aureus, officially classified as a high-priority bacterial pathogen, is very common in salted fish all around the world and should be taken into account, concerning the fact that it causes one million deaths annually and that it is also Methicillin-resistant (MRSA). Therefore, microbiological analysis of fish and salt regarding S. aureus should be recommended as obligatory in fish salting procedures by relevant authorities. Malondialdehyde (MDA) is a very reactive product of lipid oxidation, and it is very harmful because the newest researches suggest its engagement in various disease development and therefore should also be determined in all salted fish products.